THE INFLUENCE OF SMS GATEWAY ON HYPERTENSION DIET BEHAVIOR AND ENHANCEMENT OF BLOOD PRESSURE IN PROLANIS PARTICIPANTS IN UPT TALUN HEALTH CENTER BLITAR DISTRICT - Abdullah, M. Said; Sentot Imam Suprapto; M. Ali Sodiq (Universitas STRADA Indonesia, 2019)
Hypertension can be caused by unhealthy living habits such as consuming high salt, obesity, stress, smoking and alcoholic drinks. Foods that contain high sodium, high cholesterol, high fat, and high purines will enter the circulatory system which results in the emergence of plaque in blood vessels and thickens the blood so that blood circulation is not smooth which results in increased blood pressure. The purpose of this study was to determine the effect of SMS Gateway on dietary behavior and blood pressure improvement in prolanis participants at UPT. Talun Health Center, Blitar Regency. The design of this study was pre-post with control design with cross sectional approach. The population studied was all prolanis participants who had hypertension at the UPT. Talun Community Health Center in Blitar District, with an accidental sampling technique obtained a sample of 24 respondents who were divided into two control and treatment groups. The independent variable is SMS gateway, the dependent variable is dietary behavior and blood pressure. Data collection using questionnaires and observations. Data analysis using the Mann Whitney test and independent sample t test (α = 0.05). The results showed that after giving SMS gateway there were differences in dietary behavior between the treatment and posttest control groups with a significance of 0.004, there was a difference in systolic blood pressure between the treatment and posttest control groups with a significance of 0.002, and there were diastolic blood pressure differences between the treatment and post control groups. test with a significance of 0.024. The technique of giving SMS gateway is proven to be able to help respondents to pay attention to their diets, so that it is useful in efforts to control blood pressure through eating patterns and types of food.